Reflexões sobre o setor de ação educativa do Museu de Arte de Belém a partir das práticas vivenciadas no MABE – período de estágio de 2013 a 2016 - MOURA, Vivian Leticia (2019)
The museum, as an institution that acquires and preserves cultural assets of different societies, has in its preservationist functions an educational activity instituted in the process of socialization that it's developted through the exhibitions organized by the institution, whose purpose is to present to the public the collection under protection. The function of museums's education is related to their institutional objectives based on the diffusion of the knowledge produced in these institutions. Therefore, the objective of this research is to analyze the daily life of the "Ação educativa" sector in the Museu de Arte de Belém (MABE), and to problematize the effectiveness of its action for the public, as well as to identify the actions of the "Ação educativa" sector before, during and after short exposures. The approach will be in the preparation offered to the mediators and in the communication between the sector and the divisions of the Museum. To this end, a temporal cut was made corresponding the year 2016, due to the temporary exhibition conceived by the Museum, in celebration of 400 years of the foundation of the city of Belém, on January 12, 2016. The exhibition was entitled "Um Olhar Contemporâneo Sobre a Arte no Pará". The methodology used to describe the detail of the educational sector is part of the experience lived in the educational sector of the Museum. After analyzing, we can conclude that these discussions about the role of Educational Action as a sector of MABE, are necessary and contributes to improve the relationship between the Museum and the public.